Donald Shaw’s Post-Boom Paradigm and Jean Franco’s Third World Feminism: The Transformation of Love and Tradition in Laura Esquivel’s Like Water for Chocolate - Garrovillo III, Enrique Carmelo C. (Lumbini Journal of Language and Literature, 2026)
This study examines Laura Esquivel’s Like Water for Chocolate through Donald Shaw’s five Post-Boom characteristics—renewed accessibility and reader engagement, the return to the love ideal, optimism in narrative closure, incorporation of popular culture, and the emergence of marginalized viewpoints. Shaw identifies the inclusion of feminist voices as central to the Post-Boom novel but does not prescribe a specific feminist theoretical approach. Addressing this gap, the study employs Jean Franco’s Third World feminism to interpret Esquivel’s articulation of female agency, emotion, and resistance within domestic and culturally rooted spaces. The analysis argues that Esquivel fuses Post-Boom humanism with feminist subversion, transforming love, food, and family tradition into acts of rebellion against patriarchal familism grounded in colonial hierarchies. Through Tita’s defiance, Esquivel recasts passion as liberation and storytelling as continuity. The novel’s accessible narrative, moral depth, and redemptive ending exemplify Shaw’s vision of Post Boom optimism, while its feminist reworking of domesticity embodies Franco’s politics of the everyday, situating Esquivel’s work at the intersection of popular narrative, moral renewal, and cultural resistance.